2020
DOI: 10.4028/www.scientific.net/kem.861.540
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Process of Obtaining Bars from Aluminum Alloy 01417 by Combined Rolling-Extruding Method with Application of the Deform-3D Complex

Abstract: The results of computer simulation of the process of combined rolling-extruding of longish deformed semi-finished products from alloy 01417 are presented. A feature of the research is that continuously cast bars with a diameter of 12.5 mm obtained using an electromagnetic mold are used as a workpiece. This makes it possible to increase the manufacturability of processing and to obtain after rolling-extruding billets for drawing with a diameter of 5 mm with a large resource of plastic and strength properties. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…2, using the laboratory CRE-200 unit (Table 3). When modeling using the DEFORM-3D complex the following conditions were accepted: the material of the rolls and dies is absolutely rigid; the diameter of the billet is 12 mm, and the diameter of the extruded product is 5 mm; the process takes place at a constant ambient temperature of 20 ℃; the temperature of the billet is taken equal to 550 °C, and the temperature of the tool is 200 °C; for calculations, the billet was divided into 10000 finite elements; the frequency of rotation of the rolls ω varied at two levels (4 and 8 rpm); Siebel friction coefficient was: on the contact surface of the roll -a billet equal 0.8, at the border of the roll -a die equal 0.5 [21].…”
Section: Materials and Methods Of Carrying Out Researchmentioning
confidence: 99%
“…2, using the laboratory CRE-200 unit (Table 3). When modeling using the DEFORM-3D complex the following conditions were accepted: the material of the rolls and dies is absolutely rigid; the diameter of the billet is 12 mm, and the diameter of the extruded product is 5 mm; the process takes place at a constant ambient temperature of 20 ℃; the temperature of the billet is taken equal to 550 °C, and the temperature of the tool is 200 °C; for calculations, the billet was divided into 10000 finite elements; the frequency of rotation of the rolls ω varied at two levels (4 and 8 rpm); Siebel friction coefficient was: on the contact surface of the roll -a billet equal 0.8, at the border of the roll -a die equal 0.5 [21].…”
Section: Materials and Methods Of Carrying Out Researchmentioning
confidence: 99%
“…The proposed forging processes were simulated using DEFORM 3D v11.0 software. This software is specifically developed for simulating a diverse array of forging processes used in metal forming and related industries [27,28]. The diameter and height of the In the Type-I process, the head section was forged first, followed by the rod section.…”
Section: Materials Properties and Constitutive Modelmentioning
confidence: 99%
“…As studies of the methods of continuous extrusion of metals have shown [15][16][17][18][19][20][21][22][23][24], their use significantly increases the efficiency of the production of profiles from non-ferrous metals. One of the promising directions in the development of these technologies is the combination of continuous casting with extrusion on a Conform installation with a horizontal carousel mold [21][22][23][24][25][26]. During the operation of the installation, the metal melt is fed through the batcher into the annular groove of the rotating mold wheel and solidifies to contact with the stationary part of the container, formed at the interface of the groove with the arcuate segment (Fig.…”
Section: Introductionmentioning
confidence: 99%